The generation of element transfer eigenvector and application of hierarchical information recognition - Lin, Menglei; Chen, Baohui (Utilitas Mathematica, 2011)
Based on element transfer of S-rough sets.the concept of element transfer eigenvector generation is given, and characteristic theorems of element transfer are presented. By using these results, the hierarchical attribute recognition of element transfer and the sequencing method of recognition are proposed. Finally, one of its applications is given.